2021
DOI: 10.1080/13545701.2020.1853789
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Self-Reported Stress and Health Behaviors of Doctors in Kazakhstan During COVID-19

Abstract: This paper investigates the effect of COVID-19 on self-reported stress and anxiety and on adverse health behaviors of doctors in Kazakhstan, focusing on gender and family. Addressing the mental health of doctors is vital for both the short-and long-term health of doctors, patients, and the healthcare industry. Comparing survey responses from 2018 to 2020, results find marriage to have a protective effect on men doctors. Unmarried men are more likely to experience stress, anxiety, and engage in poor eating habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These restrictions likely led to changes in health behaviors, such as physical activity, smoking and alcohol use, interpersonal relationships, such as family dynamics, and structural factors, such as income and employment and health care access, as well as increased depression and anxiety. Although there have been studies targeting specific groups and mental health in relation to or during the COVID-19 pandemic in Kazakhstan (Bolatov et al, 2020;Bazarkulova and Compton, 2021;Crape et al, 2021;Kamkhen et al, 2022;Konstantinov et al, 2022), little is known about which specific COVID-19-related factors were associated with mental health among the general Kazakhstani population. To address this gap, we sought to examine the multilevel COVID-19 related factors associated with mental health in order to inform the country's future programmatic and policy response to this public health crisis.…”
Section: Introductionmentioning
confidence: 99%
“…These restrictions likely led to changes in health behaviors, such as physical activity, smoking and alcohol use, interpersonal relationships, such as family dynamics, and structural factors, such as income and employment and health care access, as well as increased depression and anxiety. Although there have been studies targeting specific groups and mental health in relation to or during the COVID-19 pandemic in Kazakhstan (Bolatov et al, 2020;Bazarkulova and Compton, 2021;Crape et al, 2021;Kamkhen et al, 2022;Konstantinov et al, 2022), little is known about which specific COVID-19-related factors were associated with mental health among the general Kazakhstani population. To address this gap, we sought to examine the multilevel COVID-19 related factors associated with mental health in order to inform the country's future programmatic and policy response to this public health crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Another was with respect to their own values and perspectives, as evidenced by greater appreciation for their intimates, and taking more time for self-care. Although the breadth and article demonstrates that occupational and household stressors are reported differently by males and females.Another study conducted with a sample of 466 students in the Kostanay region of Kazakhstan showed that levels of anxiety had not significantly risen since the beginning of the pandemic; female students experienced stronger fear; and there was no growth in substance use among Kazakh students[21]. The literature on the Kyrgyz population is even less readily available.…”
mentioning
confidence: 99%